Analisis Ekonomi Usaha Jasa Penyewaan Transplanter - Asmara, Sandi; Mahesa, Khoirul Muhammad Dendi; Suharyatun, Siti; Kuncoro, Sapto (abe.fp.unila.ac.id, 2024)
This study aims to analyze the economic feasibility of renting transplanters at Brigade Alat Mesin Pertanian Tegineneng. The research was conducted from February to July 2023 at Brigade Alat Mesin Pertanian Tegineneng District, Pesawaran Regency. Feasibility- parameters used include Break-Even Point (BEP), Net Present Value (NPV), Benefit-Cost Ratio (B/C Ratio), Internal Rate of Return (IRR), and Payback Period (PP). Sensitivity analysis was performed to determine the impact of changes in working days on feasibility values.The study results indicate that renting transplanters at Brigade Alat Mesin Pertanian in Tegineneng has a BEP value of 27.96 hectares per year. Based on an NPV of IDR 9,175,366 per year, a B/C Ratio of 1.02, an IRR of 20.79%, and a Payback Period of 4.84 years, the rental of transplanters at Brigade Alat Mesin Pertanian in Tegineneng is economically feasible. Sensitivity analysis of transplanter use shows significant changes with each change in working days. For 40 working days, the BEP is 27.96 hectares per year, NPV is IDR 49,559,304 per year, B/C Ratio is 1.13, IRR is 29.99%, and Payback Period is 3.98 years. For 50 working days, the BEP remains at 27.96 hectares per year, NPV is IDR 89,943,241 per year, B/C Ratio is 1.20, IRR is 34.31%, and Payback Period is 3.59 years. For 60 working days, the BEP is still 27.96 hectares per year, NPV is IDR 130,327,179 per year, B/C Ratio is 1.26, IRR is 36.81%, and Payback Period is 3.37 years. Keywords: BEP, B/C Ratio, IRR, NPV, Payback Period, Rice Transplanter.